Standpoint theory, situated knowledge and the situated imagination - Stoetzler, Marcel; Yuval-Davis, Nira (Feminist Theory, 2002)
The aim of the article is to further assess and develop feminist standpoint theory by introducing the notion of the ‘situated imagination’ as constituting an important part of this theory as well as that of ‘situated knowledge’. The article argues that the faculty of the imagination constructs as well as transforms, challenges and supersedes both existing knowledge and social reality. However, like knowledge, it is crucial to theorize the imagination as situated, that is, as shaped and conditioned (although not determined) by social positioning.
Keywords: approches et analyses; cours; discipline; fem1000; justice sociale; militance; mouvements sociaux; point de vue situé; premier cycle; ressource en ligne; sciences humaines; thématiques; théories féministes; épistémologie